Portray from "him" to "her": Case Study on Media Practices and Practical Significance of Chinese Female-themed Bloggers - Li, Jingwen (Transactions on Social Science, Education and Humanities Research, 2024)
The prosperity of new media and self-media has empowered women with more discourse power and influence in self-expression and group advocacy, making female-themed bloggers the emerging agents of gender communication. Through content analysis and text analysis, this paper explores the discourse expression and public influence of female-themed bloggers on social media platforms represented by "Little Red Book." It is found that female-themed bloggers have achieved considerable communication effects by shaping a high sense of social responsibility, ingenious topic planning and issue construction, creative narrative strategies, and text content focusing on women, continuously awakening women’s consciousness and promoting gender equality. The article also identifies issues in the immature stage of the female-themed communication ecosystem, uneven content quality, and evident information cocoons, and provides corresponding recommendations.